Dana Talangan Haji dan Umrah dalam Sudut Pandang Pendidikan Agama Islam - Yulianto; Abdul Manan; Uswatun Hasanah (Universitas Islam Lamongan, 2025)
This research aims to analyze the concept of Hajj and Umrah bailout funds from the perspective of Islamic religious education and assess its conformity with sharia principles. The type of research is qualitative with a literature study approach to analyze the Hajj and Umrah bailout funds from the perspective of Islamic religious education. The data collected comes from the latest research in the last five years which discusses aspects of Islamic law, maqāṣid al-sharīʿah, as well as the social and economic implications of this financing scheme. The analysis in this research was carried out using a descriptive-analytical approach. The research results show that the Hajj and Umrah bailout funds are a financing scheme that makes it easy for prospective pilgrims to obtain portions of the Hajj or Umrah departure. According to Islamic law, the bailout financing scheme using the qard wal ijarah agreement still causes controversy. Some scholars state that the addition of administrative costs in the contract resembles usury if it does not have a clear justification. Therefore, strict supervision is needed in the implementation of this sharia financial product so that it does not deviate from the principle of maqāṣid al-sharī’ah, which emphasizes the welfare of the people